Vagus nerve stimulation for treating developmental and epileptic encephalopathy in young children - Geng, Guifu; Hu, Wandong; Meng, Yao; Zhang, Huan; Zhang, Hongwei; Chen, Chuanmei; Zhang, Yanqing; Gao, Zaifen; Liu, Yong; Shi, Jianguo (Frontiers in Neurology, 2023)
Objective To investigate the clinical variables that might predict the outcome of developmental and epileptic encephalopathy (DEE) after vagus nerve stimulation (VNS) therapy and identify the risk factors for poor long-term outcome. Patients and methods We retrospectively studied 32 consecutive children with drug-resistant DEE who had undergone VNS surgery from April 2019 to July 2021, which were not suitable for corpus callosotomy. In spite of combining valproic acid, levetiracetam, lamotrigine, topiramate, etc. (standard anti-seizure medicine available in China) it has not been possible to effectively reduce seizures in the population we investigate (Cannabidiol and brivaracetam were not available in China). A responder was defined as a frequency reduction decrease > 50%. Seizure freedom was defined as freedom from seizures for at least 6 months. Sex, electroencephalograph (EEG) group, neurodevelopment, time lag, gene mutation, magnetic resonance imaging (MRI), and epilepsy syndrome were analyzed with Fisher's exact test, The age at onset and age at VNS therapy were analyzed with Kruskal-Wallis test, statistical significance was defined as p < 0.05. And used the effect size to correction. Results Among the 32 patients, the median age at VNS implantation was 4.7 years (range: 1–12 years). At the most recent follow-up, five children (15.6%) were seizure-free and 22 (68.8%) were responders. Univariate analysis demonstrated that the responders were significantly associated with mild development delay/intellectual disability (p = 0.044; phi coefficient = 0.357) and a multifocal EEG pattern (p = 0.022; phi coefficient = −0.405). Kaplan-Meier survival analyses demonstrated that a multifocal EEG pattern (p = 0.049) and DEE without epileptic spasm (ES) (p = 0.012) were statistically significant (p = 0.030). Multivariate analysis demonstrated that DEE with ES had significant predictive value for poor long-term outcome (p = 0.014, hazard ratio = 5.433, confidence interval = 1.402–21.058). Conclusions Our study suggested that VNS was a generally effective adjunct treatment for DEE. Although the predictive factors for VNS efficacy remain unclear, it should be emphasized that patients with ES are not suitable candidates for epilepsy surgery. Further investigations are needed to validate the present results.